The Role of Motivation and Spiritual Meaning in Predicting Bullying Behavior among Islamic Boarding School Students - Khamida Khamida; Fifi Khoirul Fitriyah; Hafid Algristian; Nur Hidaayah; Andikawati Fitriasari; Chuma Mohamed Muhibu; Iskandar (Nazhruna: Jurnal Pendidikan Islam, 2026)
Islamic boarding schools, known as pesantren, offer a distinctive educational experience where learning is intertwined with religious growth and community life. This research aims to evaluate the impact of school well-being and social support on the tendency for bullying in Islamic boarding schools. Specifically, the study investigates how personal motives and the perceived religious importance inherent in the pedagogical practices of these campuses can predict bullying behavior within the unique social environment and disciplinary system of pesantren institutions. We conducted interviews with 300 students across various pesantren. The cross-sectional survey utilized structural equation modeling (SEM). The findings indicate that personal qualities significantly predict an individual's spiritual meaning (β = 0.21, T = 3.18, p < 0.01) but do not directly relate to motivation or interest experience. In the context of pesantren, spiritual meaning is positively associated with these factors (β = 0.19, T = 2.87, p < 0.01). Spiritual factors significantly enhance motivation (β = 0.34, T = 5.62, p < 0.001) and spiritual meaning (β = 0.41, T = 6.48, p < 0.001). Social support emerges as the most reliable predictor of motivation (β = 0.38, T = 6.11, p < 0.001), interest experience (β = 0.29, T = 4.57, p < 0.001), and spiritual meaning (β = 0.26, T = 4.02, p < 0.001). Notably, interest experience negatively predicts bullying behavior (β = −0.31, T = 4.89, p < 0.001). These results underscore the crucial role of community and spiritual support in enhancing students' well-being and reducing harmful activities in pesantren.